2022
DOI: 10.3389/fphar.2022.1040504
|View full text |Cite
|
Sign up to set email alerts
|

Based on network pharmacology and molecular docking to explore the protective effect of Epimedii Folium extract on cisplatin-induced intestinal injury in mice

Abstract: Background: Epimedii Folium, as a natural botanical medicine, has been reported to have protective effects on intestinal diseases by modulating multiple signaling pathways. This study aimed to explore the potential targets and molecular mechanisms of Epimedii Folium extract (EFE) against cisplatin-induced intestinal injury through network pharmacology, molecular docking, and animal experiments.Methods: Network pharmacology was used to predict potential candidate targets and related signaling pathways. Molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In this work, the main active components of Csrer were analysed by UPLC-Q-Orbitrap MS. Network analysis was then used to predict targets and pathways. Moreover, molecular docking and simulations can predict ligand-receptor interactions and binding capacity (Tong et al, 2021;Hou et al, 2022;Wang et al, 2022;Xia et al, 2022). Furthermore, we verified the pharmacologic and mechanism of Csrer on LPS-induced ALI/ARDS in mice experiments.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this work, the main active components of Csrer were analysed by UPLC-Q-Orbitrap MS. Network analysis was then used to predict targets and pathways. Moreover, molecular docking and simulations can predict ligand-receptor interactions and binding capacity (Tong et al, 2021;Hou et al, 2022;Wang et al, 2022;Xia et al, 2022). Furthermore, we verified the pharmacologic and mechanism of Csrer on LPS-induced ALI/ARDS in mice experiments.…”
Section: Introductionmentioning
confidence: 59%
“…Oxidative stress and ROS overexpression are essential for developing ALI (Zhang et al, 2021;Liang et al, 2022a). Based on previous studies, SOD and MDA are critical enzymes in maintaining ROS balance (Xia et al, 2022). In the present study, ELISA was used to detect the activities of ROS, SOD and MDA in lung tissue.…”
Section: Csrer Alleviates Ali By Inhibiting Rosmediated the P53 Prote...mentioning
confidence: 93%
“…In order to clearly demonstrate the docking profile of these aggregation inhibitors, we selected a binding energy threshold of − 5 kcal/mol. This threshold was also utilized in another study [45] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A study on the intestinal barrier function of Epimedium in piglets found that Epimedium could reduce the incidence of diarrhea, and regulate the NF-kB signaling pathway and intestinal microbiome, which effectively enhances intestinal barrier function [ 47 ]. Epimedii Folium extract could significantly attenuate cisplatin-induced intestinal damage by regulating oxidative stress, inflammation, and apoptosis, and the molecular mechanism of action might be mainly related to PI3K/Akt, p53, and NF-κB signaling pathways [ 45 ]. Achyranthes bidentata peptides play a neuroprotective role in cultured hippocampal neurons by inhibiting glutamate receptor overactivation and inhibiting Caspase-3-dependent mitochondrial apoptosis pathways [ 30 ].…”
Section: Discussionmentioning
confidence: 99%